2022
DOI: 10.1002/advs.202105240
|View full text |Cite
|
Sign up to set email alerts
|

Local Release of TGF‐β Inhibitor Modulates Tumor‐Associated Neutrophils and Enhances Pancreatic Cancer Response to Combined Irreversible Electroporation and Immunotherapy

Abstract: Pancreatic cancer is a deadly disease with little response to standard therapies. Irreversible electroporation (IRE) has emerged as a novel ablative technique for the clinical treatment of pancreatic cancer. Combinations of IRE and immunotherapies, including anti-programmed death 1 (𝜶PD1) immune checkpoint blockade, have shown promising efficacy in both preclinical and clinical studies. However, tumor recurrence remains an obstacle that needs to be overcome. It herein is shown that IRE induces a substantial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…Some researchers raised the N1 and N2 terms to define neutrophils with pro‐inflammatory and anti‐inflammatory features, respectively. [ 12 ] By applying marker genes of N1 and N2, we found that most of N1‐associated genes were significantly down‐regulated in Neu‐ Setd2 KO compared to Neu‐ Setd2 WT , such as Tnfa , Ifng, Nos2 , Icam1 , Cxcl9 , and Cxcl10 . Moreover, some N2‐associated genes like Mrc1 , Il10 , and Ccl7 were further upregulated in Neu‐ Setd2 KO compared to Neu‐ Setd2 WT (Figure S4F , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers raised the N1 and N2 terms to define neutrophils with pro‐inflammatory and anti‐inflammatory features, respectively. [ 12 ] By applying marker genes of N1 and N2, we found that most of N1‐associated genes were significantly down‐regulated in Neu‐ Setd2 KO compared to Neu‐ Setd2 WT , such as Tnfa , Ifng, Nos2 , Icam1 , Cxcl9 , and Cxcl10 . Moreover, some N2‐associated genes like Mrc1 , Il10 , and Ccl7 were further upregulated in Neu‐ Setd2 KO compared to Neu‐ Setd2 WT (Figure S4F , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For example, mesoporous silica nanoparticles loaded with SB525334, an inhibitor of the TGF-β1 receptor, were designed in mouse models of pancreatic cancer. Local inhibition of TGF-β increases neutrophil polarization towards an anticancer phenotype in the TME and induces long-term antitumor memory ( Peng et al, 2022 ). Similarly, another study revealed that a novel CRC-derived exosomal circPACRGL facilitated TGF-β1 expression and induced differentiation of N1 to N2 in mouse models ( Shang et al, 2020 ).…”
Section: Strategies For Targeting Neutrophilsmentioning
confidence: 99%
“…Transforming growth factor-beta1 (TGF-β1) is a critical cytokine in the activation of CAFs and the demoplastic transformation of pancreatic tumors. Reducing the production of TGF-β1 or blockade of its relative signaling pathways represents a potent approach to downregulate stromal obstacles and enhances the penetration of chemotherapeutic drugs. , …”
Section: Introductionmentioning
confidence: 99%
“…Reducing the production of TGF-β1 or blockade of its relative signaling pathways represents a potent approach to downregulate stromal obstacles and enhances the penetration of chemotherapeutic drugs. 28,29 Angiotensin receptor blockers (ARBs) and angiotensinconverting enzyme inhibitor (ACEI) make up a group of hypertension drugs commonly prescribed in clinical applications. 30,31 Captopril is a common ACEI, which exerts therapeutic functions via Smad (abbreviation for drosophila mothers against decapentaplegic protein) and other signaling pathways.…”
Section: Introductionmentioning
confidence: 99%